2006
DOI: 10.1108/01425450710714487
|View full text |Cite
|
Sign up to set email alerts
|

Psychological contract assessment after a major organizational change

Abstract: Enhancing the success of mergers and acquisitions: an organizational culture perspective", Management Decision, Vol. 41 Iss 5 pp. 511-522 http:// dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 109 publications
(175 reference statements)
2
88
0
3
Order By: Relevance
“…To summarise, the majority of respondents (58%) indicated that they did not trust their organisation to look after their best interests. This study of merged organisations, confirmed Bellou's (2007) findings that both organisational obligations and contributions changed during mergers and acquisitions.…”
Section: Strongly Agree 10%supporting
confidence: 76%
See 1 more Smart Citation
“…To summarise, the majority of respondents (58%) indicated that they did not trust their organisation to look after their best interests. This study of merged organisations, confirmed Bellou's (2007) findings that both organisational obligations and contributions changed during mergers and acquisitions.…”
Section: Strongly Agree 10%supporting
confidence: 76%
“…Research has repeatedly shown that communication, job security, work-role stability and social support become more valuable during times of change and restructuring (Bellou, 2007), largely to allay the fears of workers. Employees become preoccupied with questions regarding what will happen to the organisation's structure, who they will be reporting to, how communication patterns will change and how restructuring will affect their pay and benefits (Bligh & Carsten, 2005).…”
Section: Organisational Restructuring and The Psychological Contractmentioning
confidence: 99%
“…The psychological contract is concluded when one party decides that it has been made a promise of future payoffs and clearly understands what the promise and contracts of exchange are about (Bellou 2007). The nature of the psychological contract and who its participants are have been analyzed from many perspectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others still assert that the psychological contract is founded on the norm of reciprocality (Cullinane and Dundon 2006). In all of these cases, in conceptualizing work expectations and responsibilities as well as the ways of handling them, either the employee or the employer follows a mental model or schema of employment relationships (Rousseau 2001, Bellou 2007). The psychological contract, therefore, determines the propensity and opportunities to create and share knowledge, as well as plotting a course of knowledge development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…What makes the psychological contract difficult to manage is that it is subjective (DelCampo, 2007;King, 2000;Robinson & Rousseau, 1994;Rousseau & WadeBenzoni, 1994), dynamic (DelCampo, 2007;Lester, Kickul, & Bergmann, 2007;Robinson & Rousseau, 1994), and idiosyncratic (Bellou, 2007;DelCampo, 2007). No two employees will share the same psychological contract.…”
Section: The Psychological Contractmentioning
confidence: 99%